Exercise-Based VRT Shows Benefits in Balance and Postural Stability in Adult Patients with Unilateral Vestibular Hypofunction - Angali, Kambiz Ahmadi; Bayat, Arash; Saki, Nader; Mirmomeni, Golshan (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
Background and Objective: Vestibular rehabilitation therapy (VRT) is an exercise-based program designed to improve balance function and alleviate problems related to dizziness, including vestibular hypofunction. This study aimed to evaluate the therapeutic effects of VRT exercises on balance function in adults with unilateral vestibular hypofunction (UVH). Methods: Thirty-one patients (mean age: 39.48 (±10.96) years old) with confirmed UVH participated in this study. The VRT program consisted of habituation and adaptation exercises in combination with gait and balance exercises. The handicapping influences of dizziness were measured with a dizziness handicap inventory (DHI) scale to measure the level of respondent’s performance on physical, emotional, and functional dimensions. Visual analogue scale (VAS) was also used to rate the severity of dizziness symptoms. The DHI and VAS scales were assessed pre-intervention and post-intervention at one, two, and four weeks follow-ups after the last rehabilitation session. Results: An analysis of variance showed a significant reduction and a consequent improvement in DHI scores after vestibular exercises in all domains: emotional, physical and functional (p < 0.001). The mean total DHI score significantly decreased by 15 points after one week, 24 points after two weeks and 15 points after four weeks of the last VRT session. The mean baseline VAS score was 7.71 (±0.91) that significantly decreased at one, two, and four weeks post-intervention to 4.81 (±0.73), 3.77 (±0.61), and 3.16 (±0.97), respectively (p<0.001). Conclusion: The exercise-based VRT shows benefits for adult patients with chronic dizziness concerning improvement in the vertigo symptom scale, fall risk, balance and emotional status.